The Productivity Improvement Effort of UMM Medical Center (UMC) Pharmacy from Customers Perspectives - Hidayati, Ika Ratna (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2016)
Introduction: The success measurement of management application in an organization or company can be seen from the company or organization’s productivity. Customer perspective used to measure productivity is by looking patients’ satisfaction by measuring importance and performance matrices and customers growth. Objectives: To identify the performance achievement in UMM Medical Center (UMC) pharmacy, by measuring the customers perspectives. Methods: This research is using the research design of non experimental case study, descriptive analysis of the data obtained. Data were gathered retrospectively and prospectively. Retrospective data to figure the customers growth, as for prospective data to find out the customer satisfaction by importance and performance matrix. Results: Results indicated that: a) customers are not satisfied by the service in the pharmacy indicated by total servqual values of -0,227, b) dimensions of tangibles, reliability, responsiveness, and assurance currently are meeting the expectations of the customers and make customers feel satisfied towards the quality of service, c) there is no increase of Customer growth (0%) during year 2014 and 2015.Conclusion: The productivity improvement efforts of Pharmacy in UMC from customers perspective are not achieved optimally, the productivity improvement is needed.